Coloration of Flowers by Flavonoids and Consequences of pH Dependent Absorption - Stavenga, Doekele G.; Leertouwer, Hein L.; Dudek, Bettina; van der Kooi, Casper J. (Frontiers in Plant Science, 2021)
Flavonoid pigments are key determinants of flower colors. As absorption spectra of flavonoids are known to be severely pH-dependent, cellular pH will play a crucial role in flower coloration. The flavonoids are concentrated in the vacuoles of the flowers’ epidermal cells, and thus the pigments’ absorption spectra are modulated by the vacuolar pH. Here we study the pH dependence of flavonoid absorption spectra in extracts from flowers of two poppy species Papaver dubium (red) and Meconopsis cambrica (orange), and a white and red Mandevilla sanderi variety. In the red poppy and Mandevilla flowers, absorption spectra of the cyanidin- and pelargonidin-based anthocyanins peak in the blue-green-wavelength range at low pH, but exhibit a distinct bathochromic shift at higher pH. This shift to longer wavelengths is not found for the blue-absorbing nudicaulin derivatives of M. cambrica, which have a similar absorption spectrum at low and high pH. The pH-dependent absorption changes of the white M. sanderi’s flavonoid remained restricted to the UV. An analysis of the spectra with logistic functions suggests that the pH-dependent characteristics of the basic states of flavonols and anthocyanins are related. The implications of tuning of pH and pigment absorption spectra for studies on flower color evolution are discussed.